The Strategy For Development of Village-Owned Enterprises in Gaura Village, West Laboya, West Sumba District - Handrianus Laka, Yohanes; Nanga, Emilia (International Research & Development for Human Beings (IRDH), 2024)
The problem formulation to be studied in this research is the Strategy for the Development of Village-Owned Enterprises in Gaura Village, West Laboya District, West Sumba Regency. This research aims to determine the Development Strategy for Village-Owned Enterprises in Gaura Village, West Laboya District, West Sumba Regency. The approach used is a qualitative approach with a descriptive research type. The data sources in this research are primary data sources and secondary data sources by using data collection techniques in the form of observation, interviews, and documentation. The results of the research show that the development strategy in developing business entities owned by Hawungo Ate Village, Gaura Village is to develop laying hens by selling or marketing, developing markets, and developing innovation. The strength of this chicken laying business is its strategic location which can be reached by the people of Gaura village and people from other villages. In terms of opportunities, there is no laying chicken business in Gaura Village, only BUMDes Hawungo Ate manages it, meaning there is no competition. Based on the results of the research and discussion that have been described, the conclusion obtained from the research results is that the strategy for developing Village-Owned Enterprises (BUMDes) in Gaura Village, West Laboya District in developing its business is that the strategy that has been implemented can maintain its contribution to BUMDes by producing a profits from the products being marketed.